1993
DOI: 10.1007/bf00196962
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ribulose-1,5-bisphosphate carboxylase-oxygenase in transgenic tobacco transformed with ?antisense? rbcS

Abstract: Abstract. Tobacco (Nicotiana tabacum L.) plants transformed with 'antisense' rbcS to decrease the expression of ribulose-l,5-bisphosphate carboxylase-oxygenase (Rubisco) have been used to investigate the contribution of Rubisco to the control of photosynthesis in plants growing at different irradiances. Tobacco plants were grown in controlled-climate chambers under ambient CO2 at 20~ at 100, 300 and 750 gmol.m 2.s-1 irradiance, and at 28~ at 100, 300 and 1000 Dmol.m 2. s-I irradiance. (i) Measurement of photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 69 publications
8
46
0
1
Order By: Relevance
“…These analyses revealed that under high-irradiance conditions, similar to those in the present experiments, Rubisco activity is primarily limiting for photosynthesis but that control is also shared with other factors. Stomatal conductance is one of these factors , and CO 2 diffusion through the aqueous phase of the leaf may be another (Lauerer et al, 1993). Our results are consistent with these conclusions and suggest that the control exerted by Rubisco on photosynthesis is considerable throughout leaf development.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These analyses revealed that under high-irradiance conditions, similar to those in the present experiments, Rubisco activity is primarily limiting for photosynthesis but that control is also shared with other factors. Stomatal conductance is one of these factors , and CO 2 diffusion through the aqueous phase of the leaf may be another (Lauerer et al, 1993). Our results are consistent with these conclusions and suggest that the control exerted by Rubisco on photosynthesis is considerable throughout leaf development.…”
Section: Discussionsupporting
confidence: 90%
“…Because the alterations in stomatal conductance are not accompanied by corresponding changes in Ci, it is unlikely that stomatal aperture plays a central role in controlling photosynthetic activity during WT and antisense leaf development, at least under these conditions (reviewed by Farquhar and Sharkey, 1982). The data in Figure 2, B and C, confirm and extend earlier observations of enhanced stomatal conductances and Ci in first fully expanded leaves of the antisense versus WT plants under high-irradiance conditions (Quick et al, 1991b;Stitt et al, 1991;Lauerer et al, 1993). Figure 3A shows that total Chl contents and the patterns of change in Chl accumulation are similar during WT and antisense leaf development.…”
Section: Photosynthetic Activitiessupporting
confidence: 85%
See 2 more Smart Citations
“…If source strength was the only factor involved in determining the developmental changes observed in the Rubisco antisense plants, then it would be expected that the SBPase antisense plants would display a similar phenotypic response. It has been shown that reductions in Rubisco result in changes in the N status of the leaves therefore it is possible that the changes in leaf development, observed in the Rubisco antisense plants, were due to a change in the C/N balance (Fichtener et al 1993;Masle et al 1993;Matt et al 2002). Further support for this suggestion comes from the finding that nitrogen reallocation occurs in the Rubisco antisense plants grown under low light conditions (Lauerer et al 1993).…”
Section: Discussionmentioning
confidence: 96%